The prospect of tumor microenvironment-modulating therapeutical strategies - Eulberg, Dirk; Frömming, Anna; Lapid, Kfir; Mangasarian, Aram; Barak, Avital (Frontiers in Oncology, 2022)
Multiple mechanisms promote tumor prosperity, which does not only depend on cell-autonomous, inherent abnormal characteristics of the malignant cells that facilitate rapid cell division and tumor expansion. The neoplastic tissue is embedded in a supportive and dynamic tumor microenvironment (TME) that nurtures and protects the malignant cells, maintaining and perpetuating malignant cell expansion. The TME consists of different elements, such as atypical vasculature, various innate and adaptive immune cells with immunosuppressive or pro-inflammatory properties, altered extracellular matrix (ECM), activated stromal cells, and a wide range of secreted/stroma-tethered bioactive molecules that contribute to malignancy, directly or indirectly. In this review, we describe the various TME components and provide examples of anti-cancer therapies and novel drugs under development that aim to target these components rather than the intrinsic processes within the malignant cells. Combinatory TME-modulating therapeutic strategies may be required to overcome the resistance to current treatment options and prevent tumor recurrence.